Molecular characterization of putative virulence determinants and identification of specific immunogenic polypeptides for the serological diagnosis of burkholderia pseudomallei infections / Puah Suat Moi - Puah, Suat Moi (2014)
The Gram-negative saprophyte Burkholderia pseudomallei is the causative agent of melioidosis, an infectious disease which is endemic in Southeast Asia and northern Australia. This bacterium possesses many virulence factors which are thought to contribute to its survival and pathogenicity. Six genes BPSL2033, BP1026B_I2784, BP1026B_I2780, BURPS1106A_A0094, BURPS1106A_1131 and BURPS1710A_1419 were identified earlier in a screen by PCR-based subtractive hybridization, using a virulent clinical isolate of B. pseudomallei and a laboratory-acquired attenuated strain of the same isolate of B. pseudomallei. Therefore, the first objective of this study was to extensively characterize these genes at the molecular level, as well as one additional gene BPSL3147 identified by other investigators. Through a reverse genetic approach, single-gene knockout mutants were successfully constructed by using site-specific insertion mutagenesis and confirmed by PCR. Likewise, complemented strains were successfully obtained by reintroducing an intact copy of the defective gene into the corresponding mutant strains. BPSL2033::Km and BURPS1710A_1419::Km mutants showed reduced survival inside macrophage RAW 264.7 cells and also low attenuation level in the virulence of nematode infection model. However, BPSL2033::Km only demonstrated a weak statistical significance (p=0.049) of intracellular survival compared to the wild type at 8 hour post infection in macrophage infection study but BURPS1710A_1419::Km showed a p-value of 0.165. Nevertheless, complemented strains of both genes were able to partially restore the gene defect both in vitro and in vivo studies, thus suggesting that they individually play a minor role in the virulence of B. pseudomallei. Lack of a universally acceptable antigen for serodiagnosis of infections caused by B. pseudomallei is another clinical challenge. The second objective of this study was to search for an immunogen via a shotgun expression library created from clinically confirmed local virulent isolates of B. pseudomallei. After 2 rounds of immunoscreening with sera from melioidosis patients, 6 sero-positive clones expressing immunogenic polypeptides were sequenced and their identities were: BPSS1904 (benzoate 1,2-dioxygenase beta subunit), BURPS1710b_0454 (a putative 200 kDa antigen p200), BPSS1856 (phosphotransferase enzyme family protein), BPSS0897 (short chain dehydrogenase), BPSL3130 and BPSS1757 (hypothetical proteins). These immunogenic polypeptides were then purified and transferred to an ELISA platform for further large scale screening. Experimental screening using 60 melioidosis positive and 123 non-melioidosis sera allowed the identification of 2 immunogenic polypeptides BPSS1904 and BPSL3130 with diagnostic potential, which demonstrated sensitivities of 75% and 90%, and specificities of 90.24% and 88.62%, respectively. The results suggest that both are potential candidate antigens for the serodiagnosis of infections caused by B. pseudomallei. In summary, the present study suggests that BPSL2033 and BURPS1710A_1419 genes to be associated with virulence of B. pseudomallei, while immunogenic polypeptides BPSS1904 and BPSL3130 were shown to be potential antigens for the serological diagnosis of its infection.